Penggunaan Kemasan Snack Ramah Lingkungan pada UMKM Kue Moci “Najah” di Kota Semarang - Yani, Tri Endang; Wibisono, Totok; Roestanto, Anantya (STIE Pelita Nusantara, 2024)
This community service stems from the discovery of Micro, Small and Medium Enterprises (MSMEs)